Prioritizing Risks and Challenges in Smart Grid Implementation: An Analytical Hierarchy Process (AHP) Approach - Al Hazza, Muataz; Sakhrieh, Lana; Farhat, Maissa; Sakhrieh, Ahmad (International Journal of Energy Economics and Policy, 2026)
As energy demand increases daily due to economic growth and population expansion, smart grid technology has emerged as an essential innovation for modern power systems. These grids integrate digital technologies, enabling real-time monitoring, control, and enhanced energy efficiency. However, deploying smart grids faces significant challenges, including cybersecurity threats, data privacy concerns, power theft, and communication infrastructure issues. This study prioritizes these challenges using the Analytical Hierarchy Process (AHP). The AHP results highlight the varying contributions of factors to smart grid risks. Cybersecurity emerges as the most critical factor (49.9%), emphasizing its role in preventing disruptions. Power theft (23.1%) significantly impacts economic and operational aspects, while data security and privacy (20%) underscore the need for robust safeguards. Communication infrastructure issues (7%) affect operations, and battery failure is identified as the least critical risk. A consistency check confirms the reliability of judgments with a Consistency Ratio (CR) below 10%. These findings help prioritize and mitigate risks effectively in smart grid systems.